Prion protein promotes copper toxicity in Wilson disease - Raffaella Petruzzelli; Federico Catalano; Roberta Crispino; Elena V. Polishchuk; Mariantonietta Elia; Antonio Masone; Giada Lavigna; Anna Grasso; Maria Battipaglia; Lucia Vittoria Sepe; Banu Akdogan; Quirin Reinold; et al. (Nature Communications)
Abstract Copper (Cu) is a vitally important micronutrient, whose balance between essential and toxic levels requires a tightly regulated network of proteins. Dysfunction in key components of this network leads to the disruption of Cu homeostasis, resulting in fatal disorders such as Wilson disease, which is caused by mutations in the hepatic Cu efflux transporter ATP7B. Unfortunately, the molecular targets for normalizing Cu homeostasis in Wilson disease remain poorly understood. Here, using genome-wide screening, we identified the cellular prion protein (PrP) as an important mediator of Cu toxicity in WD. Loss of ATP7B stimulates hepatic expression of PrP, which promotes endocytic Cu uptake, leading to toxic Cu overload. Suppression of PrP significantly reduces Cu toxicity in cell and animal models of Wilson disease. These findings highlight the critical regulatory role of PrP in copper metabolism and open new avenues for exploring the therapeutic potential of PrP suppression in Wilson disease.